ARTIFICIAL INSEMlNATION IN PENAEID SHRIMPS - PAWAR, RAVINDRA; MOHIUDDIN, M. IFTEKHAR (Journal of Indian Fisheries Association, 2015)
Artificial Insemination (AI) is a tool for genetic manipulation in the shrimp stocks. It is seen as one of the means for propagating shrimp culture to new areas by controlled reproduction. Attempts at artificial insemination in the dominant closed-thelycum penaeid shrimps species of the area viz. Metapenaeus affinis and Metapenaeus brevicornis were induced in wild adult stocks collected off Mumbai coast. Female specimens were subjected to unilateral eyestalk ablation by pinching so as to induce moulting and maturation. AI was performed two days after moulting on these females when the cuticle was still soft and flexible. Moulting also ensured rejection of initial spermatophores, if present. Response of males to electrical stimulation for spermatophore expulsion was spontaneous. Use of tissue glue for spermatophore retention was found to be unnecessary. Latency period ranged between10-16 days, while spawning occurred within 10-12 days of spermatophore transfer. Three partial spawning were recorded viz., two in Metapenaeus affinis and one in Metapenaeus brevicornis with an average spawning and hatching rates of 30% and 72.3% respectively. Average survival from first nauplius (N1) to one-day old post-larva (PLI) was a meager 3.43%. Use of AI in genetic manipulation of shrimp stocks for aquacultural purposes is indicated. Keywords : Artificial insemination, electro-ejaculation, penaeid shrimp, (glue) a-cyanoacrylate